Group analysis method for fission track thermochronology - Hadler, J. C.; Iunes, P. J.; Tello, C. A. [UNESP]; Guedes, S. (Pergamon-Elsevier B.V. Ltd, 2008)
A methodology to obtain ages and thermal histories of sets of apatite samples from localities with geologically compatible characteristics is described. A methodology exploring the fact that samples with similar geological characteristics should present the same thermal history is proposed. This approach can contribute for the obtainment of more conclusive results by analysing fewer samples than it is necessary when the samples are individually analysed. In order to determine the ages, we use the absolute neutron dosimetry through thin films of natural uranium along with lambda(f) = 8.46 x 10(-17) a(-1). As an example of application of the proposed methodology, we analyse samples collected in a Brazilian region, Sao Francisco Craton, which experienced low tectonic activity. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: thermochronology; fission track dating; apatite; neutron dosimetry; (238)U spontaneous fission; age correction